PENGARUH KEGIATAN MENGGAMBAR DENGAN TEKNIK KELERENG TERHADAP KREATIVITAS ANAK DI TAMAN KANAK-KANAK CAHAYA BUNDA - Alfi, Indah Permata; Mayar, Farida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The employment of marble technique in drawing may catch children's attention and boost their creativity and enthusiasm in drawing since they will be passionate and have their own ingenuity. This is because kindergarten students find learning to draw less engaging. Finding out how much drawing activities using marble technique affect the creativity of the kids at Cahaya Bunda Kindergarten was the aim of this research. This study's technique combined a quasi-experimental design with a quantitative approach. 36 Kindergarten-aged youngsters made up the research population, and the sample was divided into two classes, B1 and B2, each with 12 pupils. We made sure the data was uniform and normal before analysing it using the t-test. The Windows SPSS 22 program was then used to process this data. The research found that the experimental class scored an average of 18.75 on the pre-test and 23.58 on the post-test. Prior to and after the intervention, the control group's average scores were 14.83 and 16.83, respectively. The final data set showed a consistent and normal distribution. Based on the hypothesis test findings, the threshold of significance is 0.000 < 0.05. Since Ha and Ho are rejected, it might be said that the marble method fosters children's inventiveness.